Short-term spinal cord stimulation in treating disorders of consciousness monitored by resting-state fMRI and qEEG: The first case report - Yang, Yi; He, Qiheng; He, Jianghong (Frontiers in Neurology, 2022)
Disorders of consciousness (DOC) are one of the most frequent complications in patients after severe brain injury, mainly caused by trauma, stroke, and anoxia. With the development of neuromodulation techniques, novel therapies including deep brain stimulation (DBS) and spinal cord stimulation (SCS) have been employed to treat DOC. Here, we report the case of a DOC patient receiving short-term SCS (st-SCS) treatment and showing improvement monitored by resting-state fMRI (rs-fMRI) and quantitative EEG (qEEG). A 35-year-old male with severe traumatic brain injury remained comatose for 3 months. The patient was evaluated using JFK coma recovery scale—revised (CRS-R) and showed no improvement within 1 month. He received st-SCS surgery 93 days after the injury and the stimulation was applied the day after surgery. He regained communication according to instructions on day 21 after surgery and improved from a vegetative state/unwakefulness syndrome to an emergence from a minimally conscious state. To our knowledge, this report is the first published case of st-SCS in a patient with DOC. These results shed light that st-SCS may be effective in treating certain patients with DOC, which may reduce patients' suffering during treatment and lessen financial burden.